KERJASAMA UNICEF-UNFPA MELALUI GLOBAL PROGRAMME TO ACCELERATE TO END CHILD MARRIAGE (GPECM) DALAM MENANGANI KASUS PERKAWINAN ANAK DI UGANDA TAHUN 2016-2019 - Jefilia, Annisa Sesa; Fuadi, Ahmad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
This research analyzes the efforts of UNICEF and UNFPA in dealing with cases of high rates of child marriage in Uganda. High levels of child marriage trigger negative impacts on children in Uganda. This indicates a crisis regarding the surge in child marriage rates. UNICEF and UNFPA formed a global program to handle child marriage cases, namely the Global Program To Accelerate To End Child Marriage (GPECM). The aim of this research is to examine cooperation between UNICEF and UNFPA in handling child marriage cases in Uganda. This research uses qualitative methods, with data collection techniques through literature study and document analysis from several books, journals, articles, annual reports and websites at a group level of analysis. This research uses a Plularism perspective and International Cooperation theory. The results of this paper indicate that in handling child marriage cases in Uganda, UNICEF and UNFPA are trying to maintain stable numbers and effective roles in carrying out their global humanitarian programs. This can be seen from the efforts carried out by UNICEF and UNFPA in Uganda in 2016-2019 based on Uganda report data. Keywords: Child marriage, Violation of Children's Rights, International regime